The effect of electrical stimulation in critical patients: a meta-analysis of randomized controlled trials - Li, Lili; Li, Fei; Zhang, Xinyin; Song, Yuying; Li, Shuyan; Yao, Huiping (Frontiers in Neurology, 2024)
Objectives: While electrical stimulation has been demonstrated to improve medical research council (MRC) scores in critically ill patients, its effectiveness remains a subject of debate. This meta-analysis aimed to discuss recent insights into the effectiveness of electrical stimulation in improving muscle strength and its effects on different clinical outcomes in critically ill adults.Methods: A comprehensive search of major electronic databases, including PubMed, Cochrane Library, and Embase, was conducted from inception to June 15, 2024, to identify randomized controlled trials (RCTs) that evaluated the effects of electrical stimulation in critically ill patients. The analysis focused on comparing electrical stimulation to standard care, sham interventions, or placebo. Outcomes of interest included MRC scores, duration of mechanical ventilation (MV), mortality rate, and intensive care unit (ICU) and hospital length of stay (LOS).Results: A total of 23 RCTs, including 1798 patients, met the inclusion criteria. The findings demonstrated a significant benefit of electrical stimulation over usual care in enhancing global muscle strength, as measured by MRC scores (MD =3.62, 95% CI 0.94 to 6.30, P=0.0008, I 2 =87%). While subgroup analysis of electrical muscle stimulation (EMS) demonstrated no significant effect on ICU LOS, sensitivity analysis indicated a potential reduction in ICU LOS for both EMS (MD=-11.0, 95% CI -21.12 to -0.88, P=0.03) and electrical stimulation overall (MD=-1.02, 95% CI -1.96 to -0.08, P=0.03) compared to the control group. In addition, sensitivity analysis suggested that both electrical stimulation (MD=-2.38, 95% CI -3.81 to -0.94, P=0.001) and neuromuscular electrical stimulation (NMES) specifically (MD=-2.36, 95% CI -3.85 to -0.88, P=0.002) may contribute to a decrease in hospital LOS. No statistically significant differences were observed in mortality or duration of MV.Electrical stimulation appears to be an effective intervention for improving MRC scores in critically ill patients.However, further research is warranted to explain the potential effects of electrical stimulation on hospital LOS and ICU LOS.